Identification, Biology, and Management of Goosegrass [Eleusine indica (L.) Gaertn.] in Florida Turfgrasses - Pawel Petelewicz; Gregory E. MacDonald (EDIS)
This publication is a tool to aid turfgrass professionals, Extension specialists, and clientele in the identification and management of goosegrass in Florida turfgrasses. Written by Pawel Petelewicz and Gregory E. MacDonald, and published by the UF/IFAS Department of Agronomy, February 2025.